Efektivitas Kegiatan Field Trip Sebagai Metode Pembelajaran di Runiah School Makassar - Sri Rahayu; Sri Wahyuni Salman; Sri Rindayani; Thesa Aulia Pandung Radha; Yusuf Muhammad Nur; Eva Meizara Puspita Dewi (Faculty of Tarbiyah and Teacher Training, 2023)
Education is a process of influencing students in adapting to the environment and being able to make changes that exist in students. Field trips are a method used by students to complete certain learning experiences and are part of the school's curriculum program. This service aims to determine the effectiveness of the field trip method as a learning method at Runiah School Makassar. This service uses the pre-post test control design method and mentoring outdoor learning activities. The subjects of the service were students from grades 3 to grade 6. The measuring instrument used was in the form of questions consisting of 8 questions covering general knowledge and special knowledge questions. This measuring tool aims to measure student knowledge according to the location of field trip activities. Based on the dedication that was carried out, it gave the result that field trips were effectively carried out as a learning method by increasing general and special knowledge.